Designing a Digital Marketing Strategy for MSMEs in Nagari Tambangan through Openchart Platform-Based E-commerce - Rahma Yanti; Dinda Nesa Yolanda (Program Studi Bisnis Digital - Fakultas Ekonomi dan Bisnis Islam, 2025)
The aim of the article is to design a digital marketing strategy for Micro, Small and Medium Enterprises (MSMEs) through Openchart-based e-commerce to expand their market reach, up to the global level. However, in Nagari Tambangan, many MSMEs still adhere to traditional marketing strategies which are rarely used nowadays. As a result, the enormous potential of local superior products has not been utilized optimally, so that MSMEs are still relatively low in increasingly modern global market competition. Therefore, the aim of this research is to evaluate effective digital marketing through the use of platform-based e-commerce. The research and development (R&D) method used is the define, design, develop, describe (4D) development model. The study steps include: (1) defining the problems and needs of MSMEs related to digital marketing, (2) designing a digital marketing strategy that is integrated with e-commerce, (3) developing user-friendly and effective web-based promotional media, and (4) disseminating research findings on MSMEs in Nagari Tambangan. The results of the research conducted show that using OpenChart as an e-commerce platform really helps MSMEs in increasing product sales. Openchart's features include a display that is easy to use, according to needs, and the ability to sell products efficiently which makes a significant contribution to increasing the presence of products and sales of MSMEs. By using this platform, MSMEs can advertise their products digitally, attract many customers and maximize available resources. This research will provide practical assistance in improving the digital distribution of MSMEs in Nagari Tambanga. Additionally, this research can serve as a reference for developing digital marketing strategies such as content creation, social media utilization, and digital collaboration to enhance the success of MSME digital marketing strategies.